Brønsted basic TMMM-hydrotrope combined catalytic system for the synthesis of diverse dihydropyranochromenes in water at ambient temperature - Rajmane, Archana; Jadhav, Aishwarya; Patil, Nita; Kumbhar, Arjun (New Journal of Chemistry, 2025)
This work describes the synthesis of a range of bioactive chromenes using a solid Br & oslash;nsted organic base called `tris(morpholinomethyl)mesitylene' (TMMM). TMMM was obtained in high yields by treating tris(bromomethyl)mesitylene (TBMM) with morpholine in the presence of K2CO3 in acetonitrile at RT. It was characterized using 1H NMR and 13C NMR spectroscopy. We developed a Br & oslash;nsted base hydrotrope combined catalytic system (BBHC) by combining TMMM and a hydrotrope (sodium p-toluene sulphonate: NaPTS) for the cascade-type Knoevenagel-Michael addition reactions of various aldehydes and malononitrile with kojic acid, 4-hydroxy coumarin, dimedone, and lawsone in water. The methodology offers diversity-oriented synthesis (DOS) of dihydropyranochromenes in high yields. The BBHC catalytic system showed at least four times recyclability without appreciable loss of its activity. TMMM is an odorless, solid organic base that can be easily handled and is resistant to air and moisture. As TMMM is a solid base, it can reduce evaporation losses, improve safety and allow its easy recovery and reuse. TMMM acts as a powerful Br & oslash;nsted base that activates reactants, while an aqueous solution of NaPTS acts as a hydrotrope that increases the solubility of organic compounds in water.